Climate change mitigation strategies in fast-growing countries: The benefits of early action - Massimo Tavoni; Valentina Bosetti; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper builds on the assumption that OECD countries are (or will soon be) taking actions to reduce their greenhouse gas emissions. These actions, however, will not be sufficient to control global warming, unless developing countries also get involved in the cooperative effort to reduce GHG emissions. This paper investigates the best short-term strategies that emerging economies can adopt in reacting to OECD countries' mitigation effort, given the common long-term goal to prevent excessive warming without hampering economic growth. Results indicate that developing countries would incur substantial economic losses by following a myopic strategy that disregards climate in the short-run, and that their optimal investment behaviour is to anticipate the implementation of a climate policy by roughly 10 years. Investing in innovation ahead of time is also found to be advantageous. The degree of policy anticipation is shown to be important in determining the financial transfers of an international carbon market meant to provide incentives for the participation of developing countries. This is especially relevant for China, whose recent and foreseeable trends of investments in innovation are consistent with the adoption of domestic emission reduction obligations in 2030.
Keywords: Q54; Q55; Q43; 330; Energy-economy Modeling; Climate Policy; Developing Countries